Visual outcome of rigid gas permeable wearer in comparison to spectacle use at dr. M. Djamil Hospital Padang - Khairiah Nevrianty; Rinda Wati (Majalah Oftalmologi Indonesia, 2017)
Introduction. Rigid Gas Permeable (RGP) can correct visual acuity of anisometropia, myopia and astigmatism better than spectacles. Objective. To evaluate the visual outcome and frequencies of patient with myopia and astigmatism who wear RGP at refraction and contact lens subdivision department of ophthalmology M Djamil Hospital in Padang Methods. A cross analytic study based on medical record of 74 patients of myopia and astigmatism who wear RGP between January 2013 – December 2016. We analized the percentage of sex, age, diagnose, visual acuity before and after using spectacles, visual outcome after using RGP compare with spectacles. Result. RGP wearer founded in our study about 57 (77,0%) were female and 17 (23,0%) were male. The youngest patient is 11 years old and the oldest is 52 years old with the most common age between 16-25 (64,9%) yo. Most of respondent in this study was myopia astigmatism, with the visual acuty <3/60 on both of their eyes, and most of respondent using the correction >-6.00 Diopter in both RGP and spectacles. Visual outcome right after using RGP shows improvement better than spectacles, there was 8 respondents shows improvement visual acuity, with the spectacles 20/70-3/60, but with RGP became 20/20-20/60 in the right eye, and 6 responden with the spectacles 20/70-3/60, and with RGP became 20/20-20/60 in the left eye, and from statistical analytic is significant differences(p<0.05). Conclusion. Patient using RGP shows improvement in visual outcome better than using spectacles.